Relaxation modes in a smart system: weakly charged microemulsion and polyelectrolyte. Issue 16 (2nd November 2022) - El Khaoui, S.; Talha, L.; Khatouri, M.; Ahfir, R.; Naji, M.; Filali, M.
ABSTRACT: The dynamic light scattering technique is used to probe the relaxation modes of a smart system composed of weakly charged microemulsion and a polyelectrolyte. The complex is formed by oil in water microemulsion comprising Triton X-100 (TX100 ) as surfactant, cosurfactant (octanol), oil (decane) and Polyacrylic acid (PAA) which is a pH dependent polyelectrolyte. All the dynamic studies of the solutions were carried out in a basic medium at pH = 12. In the bare microemulsion (without PAA added), the analysis of the autocorrelation functions exhibits one relaxation mode, reflecting the Brownian motion of the particles. However, the dynamic light scattering (DLS) autocorrelation function shows the existence of two relaxation modes, fast and slow modes, in charged microemulsion mixed with PAA. The fast relaxation mode is diffusive and is associated to the collective diffusion of the charged particles. The slow mode is also diffusive but the mechanism at the origin is the subject of controversy. It is very likely that it arises from the entanglement of the network formed by the droplets of the microemulsion and the polyelectrolyte.